The Discrepancy of Curriculum 2013 in Teaching and Learning Process Based on Permendikbud No 65 of 2013 in SD Laboratorium Undiksha - Widyani, Ni Luh Sadewi; Suwatra, Ign. I Wyn.; Widiana, I Wayan (LPPM Undiksha, 2017)
This research aimed to determine how large the discrepancy between the ideal condition and the implementation of 2013 curriculum in teaching and learning process at SD Laboratorium Undiksha reviewed from the lesson plan, teaching learning process, assessment and learning outcomes, and the monitoring of learning process. This study was evaluative research which apply discrepancy model. Measurement of the program effectiveness was done by comparing the ideal conditions, based on Permendikbud No. 65 of 2013, with the real conditions on the implementation of 2013 Curriculum at SD Laboratorium Undiksha. Lesson plan, assessment process, and learning outcomes variable, were measured by the study documentation sheets. Meanwhile, the teaching and learning process variable was measured by observation sheets, and the monitoring of learning process variable was measured by questionnaire. Sample of the study consisted of 4 teachers of SD Laboratorium Undiksha. The scores form for all variables were analyzed using the Wilcoxon’s signed rank test. The sign difference and score difference were calculated with a predetermined standard. The result of the analysis showed that the large of discrepancy between ideal conditions (based on Permendikbud No. 65 of 2013) and the implementation of 2013 Curriculum at SD Laboratorium Undiksha in terms of lesson plan is 17,90%, teaching and learning process is 12,11%, assessment and learning outcomes is 6,67%, and the monitoring of learning process is 10,95%. The discrepancy is generally due to the difficulty in changing the mindset of most education staff, tardiness of the books’ distribution, and uneven training programs for educators.